2020
DOI: 10.1016/j.celrep.2020.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Retino-Cortical Mapping Ratio Predicts Columnar and Salt-and-Pepper Organization in Mammalian Visual Cortex

Abstract: Highlights d Determinants of columnar and salt-and-pepper patterns in visual cortex are sought d Retino-cortical mapping ratio solely predicts cortical patterns across species d Nyquist sampling model explains sharp parametric division of patterns d Controlled simulation of retino-cortical sampling ratio reproduces observed patterns

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 113 publications
(152 reference statements)
3
43
2
Order By: Relevance
“…The reason why two species have different burst synchrony can be considered in two different aspects related to RGC: (1) Difference in RGC density, and (2) Different RF size of RGC. First, for RGC density, previous studies showed that the RGC density in primate fovea is higher than that of mouse RGCs [ 55 - 57 ]. The higher the RGC density, the shorter the average distance between RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why two species have different burst synchrony can be considered in two different aspects related to RGC: (1) Difference in RGC density, and (2) Different RF size of RGC. First, for RGC density, previous studies showed that the RGC density in primate fovea is higher than that of mouse RGCs [ 55 - 57 ]. The higher the RGC density, the shorter the average distance between RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Retino-cortical feedforward projections organize a precise retinotopy in most species 34,36,37 , and visual information from a local retinal area is projected onto a local cortical space. If the size of the cortex is large, two distant cortical neurons that receive inputs from distinct retinal spaces cannot communicate because their local connections do not overlap.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the question of how the relationship between eye movement and active perceptual process can help us understand the visual circuits involved. Computational model studies suggest that diverse visual functions -from the fundamental orientation selective response [60][61][62] to complex cognitive behaviors such as face perception or working memory 48,[63][64][65] -can arise from a simple variation of the physical circuit structure. If this is the case in the present study, we can also suggest that a common neural circuit mechanism with simple variation determines both eye movement and active visual perception from the intact correlation between intrinsic eye movement and the perceptual alternation dynamics [66][67][68][69] .…”
Section: Discussionmentioning
confidence: 99%